2014
DOI: 10.1093/mnras/stu1385
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy formation as a cosmological tool – I. The galaxy merger history as a measure of cosmological parameters

Abstract: As galaxy formation and evolution over long cosmic time-scales depends to a large degree on the structure of the universe, the assembly history of galaxies is potentially a powerful approach for learning about the universe itself. In this paper we examine the merger history of dark matter halos based on the Extended Press-Schechter formalism as a function of cosmological parameters, redshift and halo mass. We calculate how major halo mergers are influenced by changes in the cosmological values of Ω m , Ω Λ , σ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 95 publications
3
33
0
Order By: Relevance
“…Conselice et al 2008;Vulcani et al 2011) As shown in previous work (e.g. Conselice et al 2008;Ilbert et al 2010;Conselice et al 2014), there is a general trend for elliptical and S0/Sa fractions at a given stellar mass to increase towards lower redshifts. These systems increasingly dominate the number density at high stellar masses towards the present day (e.g.…”
Section: /V Max Weighting and Simulation Of Uncertaintiessupporting
confidence: 66%
“…Conselice et al 2008;Vulcani et al 2011) As shown in previous work (e.g. Conselice et al 2008;Ilbert et al 2010;Conselice et al 2014), there is a general trend for elliptical and S0/Sa fractions at a given stellar mass to increase towards lower redshifts. These systems increasingly dominate the number density at high stellar masses towards the present day (e.g.…”
Section: /V Max Weighting and Simulation Of Uncertaintiessupporting
confidence: 66%
“…While in the local Universe the most powerful molecular outflows are observed in AGN-dominated merger ULIRGs, analysis of deep Hubble fields based on structural parameters indicate a merger fraction of massive (> 10 10 M ⊙ ) galaxies increasing with redshift up to 10% at z = 1.2, implying that a typical present-day massive galaxy has undergone ∼ 1 major merger during the last ∼ 9 Gyr (Conselice et al 2009;Robaina et al 2010;Xu et al 2012). This merging rate is capable of explaining the build-up of the red sequence during the last ∼ 8 Gyr (Eliche-Moral et al 2010;Xu et al 2012;Prieto et al 2013), and it is in general concordance with the ΛCDM galaxy mass assembly model (Conselice et al 2014) 3 . Alternatively, smooth cold mode accretion of intergalactic gas, which is expected from simulations to be the main gas supply for star formation over cosmic times (e.g.…”
Section: Introductionsupporting
confidence: 70%
“…We also explore four different differential pair fractions (PFs) = (df /dq)M,z, extracted from (Bundy et al 2009;de Ravel et al 2009;López-Sanjuan et al 2012;Xu et al 2012) following the same procedure as in S13 (see also detailed description in Gerosa & Sesana 2015). We checked that those broadly match recent compilations of galaxy PFs from, e.g, Conselice et al (2014). Considering different MFs and PFs helps in folding into our computation possible systematic errors due to the specific samples and techniques adopted in each work.…”
Section: Galaxy Merger Ratementioning
confidence: 99%